Pengaruh Penerapan Aplikasi Qraetif Sebagai Media Pembelajaran Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ipas Materi Tata Surya Di Sd Negeri 07 Sitiung - Nazaria, Radatul; Ahmad Ilham Asmaryadi; Estuhono (Jurnal Tunas Pendidikan, 2025)
This study was motivated by the low learning outcomes of sixth-grade students in the Science and Social Studies (IPAS) subject at SD Negeri 07 Sitiung. The aim of the study was to determine the effect of using the Qreatif application as a learning medium on students' learning outcomes in the Solar System material. This research employed a quantitative approach with an experimental design, specifically a pre-experimental method using a one-group pretest-posttest design. The population consisted of all sixth-grade students at SD Negeri 07 Sitiung, totaling 15 students. The sample was selected using a saturated sampling technique. Data collection was carried out through learning outcome tests (pretest and posttest) in the form of multiple-choice questions. Data analysis techniques included normality testing and hypothesis testing using a paired samples t-test. The results of the paired samples t-test showed a two-sided p-value of 0.000, which is less than the significance level of 0.05 (p < 0.05). According to the hypothesis testing criteria, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The hypothesis test indicated a significant difference between students’ scores before and after the treatment. Therefore, it can be concluded that the use of the Qreatif application significantly affects students’ learning outcomes in class VI at SD Negeri 07 Sitiung